(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A buoyancy coefficient measures the income responsiveness of a tax yield due to the combined effects of the automatic and the discretionary changes made in the Tax system. The yield of a tax may also go up on account of an extension of its coverage or a revision in the tax rates. Such a characteristic features of a tax related system is referred to as its elasticity. In other words, the elasticity of a tax refers to its responsiveness to steps taken by the tax authorities in increasing the tax yield through an extension of its coverage or through a revision of its tax rates. An in depth analysis has been carried out to study the sensitivity of a Tax system by computing buoyancy and elasticity coefficients of taxes. A buoyancy coefficient measures the income responsiveness of a tax yield due to the combined effects of the automatic and the discretionary changes made in the tax system. The yield of a tax may also go up on account of an extension of its coverage or a revision in the tax rates. Such a characteristic features of a tax related system is referred to as its elasticity. In other words, the elasticity of a tax refers to its responsiveness to steps taken by the tax authorities in increasing the tax yield through an extension of its coverage or through a revision of its tax rates.